The influence of mood and social relationships on the intensity of basic self-disturbance: an experience sampling method investigation - Baklund, Lise; Røssberg, Jan Ivar; Melbye, Sigurd Arne; Pesonen, Henri; Møller, Paul (Frontiers in Psychiatry, 2025)
BackgroundBasic self-disturbance (BSD), the overarching concept of various experiences of self-alienation, referred to as anomalous self-experiences (ASEs), is considered a relatively stable clinical marker for the potential development of schizophrenia spectrum disorders. However, research on BSD in children and adolescents in the pre-psychotic phase is limited. Research on individuals at risk for psychosis shows that psychosocial factors are critical in psychosis development, but studies of these factors and the relationship between psychosocial factors and the severity of ASEs are lacking. The present study aims to investigate the extent to which mood, social relationships, and psychosocial factors contribute to the development of BSD in adolescents at risk for psychosis.MethodsWe used the experience sampling method to collect real-time data from 27 help-seeking 12- to 19-year-old adolescents. We analyzed data from daily registrations on a smartphone app, measuring the intensity of BSD, mood, and social settings over various time periods (hourly, daily, and weekly over 6 months) by linear mixed regression modeling.ResultsNegative emotions were positively associated with the mean ASE scores (β = 0.30, 95% CI = (0.26, 0.34), whereas for the positive emotions, the contrast of the association was significantly negative [β = −0.57, 95% CI = (−0.63, −0.51)]. The effect of being alone at the time of the response on the intensity of ASEs compared to being with others was significantly positive [β = 0.27, 95% CI = (0.08, − 0.46)]. However, this effect was observed only when not being at home, as indicated by the effect of being at home [β = −0.04, 95% CI = (−0.09, 0.11)] compared to not being at home and the interaction between the two social context variables [β = −0.20, 95% CI = (−0.44, −0.04)].ConclusionsMood and social settings appear to be influencing factors in the expression and intensity of ASEs. These factors should be addressed in the clinical approach to BSD, and further studies investigating the influence of various psychosocial factors on BSD experiences should be conducted.